2008
DOI: 10.1039/b704580h
|View full text |Cite
|
Sign up to set email alerts
|

Understanding hygroscopic growth and phase transformation of aerosols using single particle Raman spectroscopy in an electrodynamic balance

Abstract: Hygroscopic growth is one of the most fundamental properties of atmospheric aerosols. By absorbing or evaporating water, an aerosol particle changes its size, morphology, phase, chemical composition and reactivity and other parameters such as its refractive index. These changes affect the fate and the environmental impacts of atmospheric aerosols, including global climate change. The ElectroDynamic Balance (EDB) has been widely accepted as a unique tool for measuring hygroscopic properties and for investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 63 publications
5
92
0
Order By: Relevance
“…The relative humidity in lower layer almost remains around $80% from the early evening to early morning the next day, which play a critical role in formation of 12-day fog during the observational period. It has been demonstrated that the condition of high relative humidity could promote aerosol particle to grow hygroscopicly (Hu et al, 2010) and chemical transformation (Lee et al, 2008). Therefore, it may be taken for granted that the relative humidity in Urumqi in winter is another key factor that does make important contribution to the terrible air quality.…”
Section: Observation Resultsmentioning
confidence: 99%
“…The relative humidity in lower layer almost remains around $80% from the early evening to early morning the next day, which play a critical role in formation of 12-day fog during the observational period. It has been demonstrated that the condition of high relative humidity could promote aerosol particle to grow hygroscopicly (Hu et al, 2010) and chemical transformation (Lee et al, 2008). Therefore, it may be taken for granted that the relative humidity in Urumqi in winter is another key factor that does make important contribution to the terrible air quality.…”
Section: Observation Resultsmentioning
confidence: 99%
“…Raman spectra of pure AS, pure MA, and their internal mixture with 30 wt% MA have been reported using our EDB/Raman system (Lee et al 2008;Ling and Chan 2008). As shown in Figure 6a and b, the spectra of both crystalline (<5% RH) and aqueous (80% RH) 30 wt% MA particles are the approximate superpositions of the corresponding pure AS and MA spectra approximately.…”
Section: Changes In Hygroscopicity Of Aqueous and Solid Particles Aftmentioning
confidence: 95%
“…To probe the temporal chemical changes in levitated droplets, a Raman spectroscopy system similar to the one used by Lee et al (2008) was employed. The system consisted of a 150-mW diode-pumped solid-state laser (Spectra-Physics Excelsior, 532-150-SLM-CDRH) and a 0.5-m monochromator (Acton SpectraPro 500) attached to a charge-coupled device (CCD) detector (Andor Technology DV420-OE), and was integrated with the EDB system.…”
Section: Raman Spectroscopy Of Single Levitated Particles In Edb and mentioning
confidence: 99%
“…Changes in the Raman shift magnitude during phase transitions of AS and AN have been reported by a few investigators (Musick et al 2000;Zhang and Chan 2002;Jordanov and Zellner 2006). The Raman peaks of solid particles are more intense and sharper relative to aqueous particles, so a sudden change in the fwhh (normalized to that at the lowest RH) of a distinct peak is also useful for phase identification (Lee et al 2008;Ling and Chan 2008). In this study, the changes in the fwhh and the positions of the ν 1 (SO for AN were also observed, consistent with literature reports.…”
Section: Phase Transitions Of Single-component Systemsmentioning
confidence: 98%
“…An aerosol flow tube coupled with a Fourier transform infrared (FTIR) spectrometer has been used to study phase transitions of suspended particles (Cziczo et al 1997;Onasch et al 1999). In addition, a combined EDB/Raman spectrometer (Fung and Tang 1988) has been demonstrated to provide solid spectral evidence of the phase 270 M. C. YEUNG AND C. K. CHAN state of a particle simultaneously with hygroscopicity measurements (Zhang and Chan 2002;Jordanov and Zellner 2006;Lee et al 2008;Ling and Chan 2008). More recently, micro-Raman spectroscopic systems have been employed to investigate the molecular interactions in supersaturated droplets of different inorganic species (Wang et al 2005;Li et al 2006;Dong et al 2007) and the polymorphic transformation of NH 4 NO 3 particles deposited on a hydrophobic substrate (Wu and Chan 2008).…”
Section: Introductionmentioning
confidence: 99%